Deconstructing the cloud: Responses to Big Data phenomena from social sciences, humanities and the arts. Issue 2 (28th July 2015) - Niederer, Sabine; Taudin Chabot, Raymond
The era of Big Data comes with the omnipresent metaphor of the Cloud, a term suggesting an ephemeral and seemingly endless storage space, unhindered by time and place. Similar to the satellite image of the Whole Earth, which was the icon of technological progress in the late 60s, the Cloud as a metaphor breathes the promise of technology, whilst obfuscating the hardware reality of server farms and software infrastructure necessary to enable the proliferation of (big) data. This article presents projects from the fields of humanities, social sciences and the arts that formulate a response to Big Data and its human and automated practices, from data analytics dashboards to critical reflections on smart technologies and objects.